Budaya Kekerasan dan Konflik Etnisitas di Kalimantan Barat Periode 1966-2000 - Atok, Kristianus (Borneo Review, 2022)
The background of this research is the high phenomenon of cultural violence in West Kalimantan in the period 1966-2000. The author wants to study the relationship between these phenomena and political events that occurred both at the Indonesian National level and at the regional level in West Kalimantan. The author uses the library method in collecting the necessary data, the data is then processed with the theory of culture and conflict. After conducting research for three months, the author finally concludes that the phenomenon of culture of violence in West Kalimantan stems from practical political interests carried out by ethnic elites to gain power. This phenomenon is also influenced by political events that occur at the national level. On the other hand, the strengthening of identity politics cannot be separated from the role of ethnic institutions. Institutions such as MAD (Majelis Adat Dayak) and MABM (Majelis Adat Budaya Melayu) have created a sense of ethnic pride. Sometimes the pride is excessive and even leads to ethnic militancy (ethnocentrism). Incidentally, these institutions were established before the occurrence of large-scale and massive ethnic riots. Therefore, do not be surprised if it is later associated with ethnic consolidation. Various parties then saw that ethnicity institutions greatly strengthened ethnic identity politics in West Kalimantan